What is Financial Exclusion? A Review - Devi, Abrista (SMART Insight, 2023)
The Central Bureau of Statistics (BPS) recorded that the Indonesian population living below the poverty line as of March 2016 reached 28.01 million people. Although Indonesia's poverty tended to decline in 2016, the World Bank considers that Indonesia's economic inequality has widened in the last 15 years. Poverty in Indonesia is motivated by financial exclusion. Financial exclusion is the lack of access, faced by those most in need, to cheap, fair and safe financial services from mainstream service providers. This study aims to determine the development of Financial Exclusion research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 597 indexed research publications. The data is then processed and analyzed using the VoSviewer application to determine the bibliometric map of Financial Exclusion research development.